Rapid prototyping - Cook, Jerome T.; Vaccari, John A. (Fundamental manufacturing processes)
This programme introduces the technologies, systems, and materials used to produce rapid prototype models, parts and tooling. Includes stereolithography, selective laser sintering, fused deposition modeling, ultrasonic consolidation, the pro metal system, room temperature vulcanized tooling, and various ink-jet and multi-jet systems.